In vitro assessment of bacterial strains associated with microalgae as potential probiotics - Zabidi, Aimi; Rosland, Nur Natasya Ain; Yaminudin, Jasmin; Karim, Murni (Universiti Putra Malaysia Press, 2021)
Bacteria and microalgae are essential elements in the aquatic ecosystem, co-existing and having constant interactions with each other which help microalgae to exert its beneficial effect as probiotics in aquaculture. This research aims to isolate and identify potential probiotics from different species of microalgae and to evaluate their antimicrobial activity against pathogenic Vibrio spp. via series of in vitro assays; disc diffusion, well diffusion, and co-culture assays. A total of 18 bacterial strains were isolated from five species of microalgae; Chlorella sp., Nannochloropsis sp., Amphora sp., Chaetoceros sp., and Spirulina sp.. The isolated strains were tested in in vitro antagonistic assay against four Vibrio spp. (Vibrio harveyi, Vibrio alginolyticus, Vibrio vulnificus, and Vibrio parahaemolyticus). Seventeen strains demonstrated antimicrobial activity with the highest inhibition was observed by strain SPS11 against V. parahaemolyticus (12.6 ± 0.36 mm) in disc diffusion assay and strain NAS32 showed 13.2 ± 0.45 mm clear zone against V. vulnificus in well diffusion assay. In co-culture assay, both the SPS11 and NAS32 were able to reduce the growth of V. parahaemolyticus and V. harveyi at concentration of 106 and 108 CFU mL-1, respectively. Strains SPS11 and NAS32 were characterized as gram positive bacteria with rod shape and further identified as Lysinibacillus fusiformis (SPS11) and Lysinibacillus sphaericus (NAS32) using 16s rRNA. These two strains should be further studied in in vivo challenged experiments in fish and shellfish to explore their probiotic effects.